1975
DOI: 10.1302/0301-620x.57b2.214
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Compounds in Bone Scanning

Abstract: Bone scanning with radioactive isotopes has been used to study a wide variety of disorders. Recently certain phosphate compounds, labelled with technetium, have been used as bone scanning agents. The comparative merits of three technetium-labelled phosphate compounds currently available for bone scanningpyrophosphate, tripolyphosphate and ethyiliydroxydiphosphonate (EHDP) have been compared in rabbits. Each substance was injected into ten rabbits and blood was withdrawn at regular intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been reported that the blood levels of [ 99m Tc]EHDP decreased over a period of time and the urine level increased. Hughes et al (16), investigating phosphate compounds in rabbits, demonstrated the rapid blood clearance of EHDP compared with that of pyrophosphate or tripolyphosphate. The rapid blood clearance of EHDP compared with that of polyphosphate or pyrophosphate has been confirmed in patients who have undergone bone scanning to detect metastases from breast tumors (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the blood levels of [ 99m Tc]EHDP decreased over a period of time and the urine level increased. Hughes et al (16), investigating phosphate compounds in rabbits, demonstrated the rapid blood clearance of EHDP compared with that of pyrophosphate or tripolyphosphate. The rapid blood clearance of EHDP compared with that of polyphosphate or pyrophosphate has been confirmed in patients who have undergone bone scanning to detect metastases from breast tumors (8).…”
Section: Discussionmentioning
confidence: 99%
“…with faster blood clearance. when compared with polyphosphate or pyrophosphate (Dunson et al 1973;Ackerhalt et al 1974;Krishnamurthy et al 1974 ;Hughes et al 1975). Not all reports.…”
Section: Properties Required Of a Bonescanning Agentmentioning
confidence: 99%
“…Uptake by bone differs between different phosphate compounds and is related to chain lengths for polyphosphate (1,19,20). In rabbits (15) and in man (7) diphosphonates have been shown to have a more rapid blood clearance than pyrophosphate or polyphosphate with a significant improvement in ratio of bone to soft tissue at 4 hr. The exact mechanism of bone localization of the phosphate compounds is not known, however, but it seems that the compounds bind strongly onto the bone surface by chemisorption (18).…”
mentioning
confidence: 99%